Stunting Allevation in Kalibaru Subdistrict, North Jakarta trough the Implementation of Integrated Urban Farming and Rainwater Harvesting System - Risma Anisa; Nur Khafifah Rusni; Annisa Fitri Mustafa; Hayati Sari Hasibuan; Ahyahudin Sodri; Sri Setiawati Tumuyu; Analissa Huwaina; Muhammad Hasnan Habib (Jurnal Penelitian Pendidikan IPA, 2023)
Stunting remains a serious public health problem in urban areas. A contributing factor to the high prevalence of stunting in the region is the limited availability of clean water and nutrient-rich foods. In addition, this sub-district is at risk of experiencing a clean water crisis in the future. This study aims to analyze the effectiveness of the integration of rainwater harvesting (RWH) and urban farming to overcome stunting, access to clean water, and food supply in Kalibaru District, North Jakarta. The method used is a social experiment through three processes: community education, RWH installation, and urban agricultural system development. For each process, data collection was carried out through field observations and surveys of 39 respondents. Community knowledge was measured before and after the process through questionnaires, and the results of the integration of RWH and urban farming systems were described. The results showed an increase in public knowledge about the benefits of RWH integration and urban farming. RWH has helped alleviate the problem of clean water availability effectively and economically. Meanwhile, urban agriculture has given communities better access to nutrient-rich foods, which in turn can help reduce the problem of stunting.